Near-infrared light emitting devices from Er doped silica thin films via introducing SnO2 nanocrystals. (1st December 2022) - Wang, LiXiang; Zhang, YangYi; Chen, JiaMing; Qu, EnZe; Zhao, JingJie; Li, Dongke; Li, Wei; Xu, Jun; Chen, KunJi
Abstract: To get high performance light emitting devices on Si platform with emission wavelength at 1.55 μ m is a challenge for future Si-based opto-electronic integration chips. In this paper, we fabricated near-infrared light-emitting devices based on Er/SnO2 co-doped silica thin films. The introduction of SnO2 nanocrystals with controllable size and density not only contributes to the near-infrared light emission enhancement of Er 3+ ions at 1.55 μ m, but also provides an effective carrier transport channel to realize efficient and stable electro-luminescence. The corresponding devices exhibit an external quantum efficiency of 5.4% at near infrared light region and the power efficiency is about 1.52 × 10 −3 . Our present work lays a solid foundation for facilitating Si-based light source towards practical application in the field of optoelectronic interconnection.